Memory and identity in ancient Judaism and early Christianity : a conversation with Barry Schwartz - Thatcher, Tom, 1967-; Schwartz, Barry, 1946- (Atlanta: SBL press, 2014)
"This volume applies theoretical principles, along with related aspects of Schwartz's model and the work of other significant memory theorists, to a number of case studies from ancient Jewish and early Christian history. The contributors to the present volume ask three questions of specific research problems within their individual fields of expertise: How can one separate the actual past from commemorative dressing in the extant sources, and what difference does it make to do so?; How did ancient Jews and early Christians draw upon the past to create a durable sense of communal identity, often in the face of trauma?; and, What strategies of keying and framing are evident in the extant sources, and what can these tell us about those texts and their authors and original audiences? While the contributors to the volume answer, and nuance, these questions in different ways as they address them to their respective cases in point, together they serve as the unifying theme of this book"--
Includes bibliographical references and indexes.
Keywords: Schwartz, Barry, -- 1946-; Group identity; Collective memory; Church history -- Primitive and early church, ca. 30-600.; Judaism -- History -- Post-exilic period, 586 B.C.-210 A.D.; Jews -- Identity